2006
DOI: 10.1093/geront/46.5.650
|View full text |Cite
|
Sign up to set email alerts
|

Older People's Views of Falls-Prevention Interventions in Six European Countries

Abstract: Because many older people reject the idea that they are at risk of falling, the uptake of strength and balance training programs may be promoted more effectively by maximizing and emphasizing their multiple positive benefits for health and well-being. A personal invitation from a health professional to participate is important, and it also may be helpful to provide home-based programs for those who dislike or find it difficult to attend groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
242
2
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(267 citation statements)
references
References 40 publications
19
242
2
4
Order By: Relevance
“…In group exercise such as Tai Chi, verbal and social persuasion is often provided by peers and the instructor, which itself may lead to increased social connectedness and confidence [81]. It has also been suggested that increased social support from family and peers can increase selfefficacy (belief in own ability to undertake the activity) by giving older adults the confidence to believe that they can carry out the movements [86].…”
Section: Social Impactmentioning
confidence: 99%
“…In group exercise such as Tai Chi, verbal and social persuasion is often provided by peers and the instructor, which itself may lead to increased social connectedness and confidence [81]. It has also been suggested that increased social support from family and peers can increase selfefficacy (belief in own ability to undertake the activity) by giving older adults the confidence to believe that they can carry out the movements [86].…”
Section: Social Impactmentioning
confidence: 99%
“…In diesem Zusammenhang erfolgte eine separate Recherche zu Ziel-und Wertvorstellungen älterer Menschen mit Sturzereignis oder unter Sturzrisiko. Insgesamt konnten 13 Studien identifiziert werden, davon fünf Studien mit qualitativ-explorativem Design (Carroll, Dykes, & Hurley, 2010, USA;Calhoun et al, 2011, USA;Horton, 2007, UK;Yardley et al, 2006a, DK, GER, UK, NL, CH, GR und Yardley et al, 2006b, UK) vier Surveys (Crombie et al, 2004, UK;Haines, & McPhail, 2011;Hughes et al 2008;Salkeld et al, 2000, AUS), zwei systematische Übersichtsarbeiten (Bunn, Dickinson, Barnett-Page, McInnes, & Horton, 2008;McInnes, & Askie, 2004, UK), eine Querschnittsstudie (Dorresteijn, Rixt Zijlstra, Van Eijs, Vlaeyen, & Kempen, 2012, NL) und eine Studie mit Mixed-Methods Design (Honaker, & Kretschmer, 2014, USA). Die Studien zeigen auf, dass ältere Menschen besser aufgeklärt werden und mehr über die Gründe für ihr Sturzrisiko erfahren wollen (Carroll et al, 2010).…”
Section: Klientenzentrierte Endpunkteunclassified
“…Die Studien zeigen auf, dass ältere Menschen besser aufgeklärt werden und mehr über die Gründe für ihr Sturzrisiko erfahren wollen (Carroll et al, 2010). Sie nehmen insbesondere dann an Sturzpräventionsprogrammen teil, wenn diese ihre Selbstständigkeit, Gesundheit, Autonomie, eigene Entscheidungen zu treffen und soziale Kontaktmöglichkeiten fokussieren (Calhoun et al, 2011;Carroll et al, 2010;Bunn et al, 2008;Hughes et al, 2008;Yardley et al, 2006a;McInnes, & Askie, 2004;Salkeld et al, 2000).…”
Section: Klientenzentrierte Endpunkteunclassified
See 1 more Smart Citation
“…Not recognizing (the severity of) a fall or not remembering a fall may attribute to the low uptake by older persons who are offered fall prevention programs [41][42][43], as the recognition of falls by the older persons themselves is crucial for the uptake of a fall prevention program. Another problem is that different perceptions and definitions of a fall exist between older persons, researchers, and health professionals [15,19,28].…”
Section: Perceptions Of a Fallmentioning
confidence: 99%